Higher protein intake during caloric restriction improves diet quality and attenuates loss of lean body mass. Issue 7 (11th May 2022) - Ogilvie, Anna R.; Schlussel, Yvette; Sukumar, Deeptha; Meng, Lingqiong; Shapses, Sue A.
Abstract: Objective: Higher protein intake during weight loss is associated with better health outcomes, but whether this is because of improved diet quality is not known. The purpose of this study was to examine how the change in self‐selected protein intake during caloric restriction (CR) alters diet quality and lean body mass (LBM). Methods: In this analysis of pooled data from multiple weight loss trials, 207 adults with overweight or obesity were examined before and during 6 months of CR (approximately 10 food records/person). Body composition was measured by dual‐energy x‐ray absorptiometry. Diet quality was assessed using the Healthy Eating Index in 2 groups: lower (LP) and higher (HP) protein intake. Results: Participants (mean [SD], 54 [11] years; 29 [4] kg/m 2 ) lost 5.0% (5.4%) of weight. Protein intake was 79 (9) g/d (1.0 [0.2] g/kg/d) and 58 (6) g/d (0.8 [0.1] g/kg/d) in the HP and LP groups, respectively ( p < 0.05), and there was an attenuated LBM (kilograms) loss in the HP (−0.6% [1.5%]) compared with the LP (−1.2% [1.4%]) group ( p < 0.01). The increased Healthy Eating Index score in the HP compared with the LP group was attributed to greater total protein and green vegetable intake and reduced refined grain and added‐sugar intake ( p < 0.05). Conclusions: Increasing dietary protein during CR improves diet quality and may be another reason for reduced LBM, but it requires further study.